Chemical modification of palm fibres surface with zirconium oxychloride - Martins, Giulia Araújo; Pereira, Paulo Henrique Fernandes [UNESP]; Mulinari, Daniella Regina (My University, 2013)
Chemical modification of natural fibres has been carried out using different methods for such purposes as reinforcement in polymer matrices and heavy metals adsorption. In this work, palm fibres were modified by zirconium oxychloride in situ. The palm fibres that had been chemically modified were compared to those in nature using fibres that passed through 20 and 40 mesh screens to evaluate the influence of particle size on modification. Palm fibres were modified with ZrO2.nH2O nanoparticles through the use of zirconium oxychloride in an acidic medium in the presence of palm fibres using ammonium solution (1:3) as the precipitating agent. Scanning electron microscopy (SEM), X-ray diffraction (XRD), infrared spectrophotometry (FTIR), and atomic emission spectrometry with inductively coupled plasma (ICP-AES) were used to characterize the hybrid materials. Results indicated that the particle size of the palm fibres influenced in the modification, because the fibres with smaller particle size had a greater deposition of inorganic material. The ICP technique revealed an increase of 21% nanoparticles ZrO2.nH2O deposited on fibres (40 mesh) when compared to fibres (20 mesh). The diameter of nanoparticles ZrO2.nH2O deposited on fibres was about 50 to 220 nm, as observed by SEM.
Keywords: Hydrous zirconium oxide; Nanocomposites; Palm fibres